INSIGHT FROM NANOMATERIALS AND NANOTECHNOLOGY TOWARDS COVID-19 - Liqaa Y. Mohsen; Rafal Ahmed Lilo; Zeena Hadi Obaid Alwan; Zahraa Saleh Kamil (Web of Journals Publishing, 2024)
There have been concerns expressed about SARS-CoV-2's enhanced capacity to elude the six COVID-19 vaccine candidates that are now under approval, as well as antibodies' decreasing ability to neutralize it. SARS-CoV-2 variants include B.1.1.529 for Omicron, B.1.617.2 for Delta, and B.1.1.7 for UK, B.1.351 for South Africa, P.1 for Brazil, and B.1.6.17 for India. According to this perspective, in order to assess the existing obstacles and pave the way for a more stable and feasible future for the development of vaccines against SARS-CoV-2 and other pandemics, countries should conduct early effectiveness studies prior to initiating broad vaccination campaigns. The role of nanoparticles as vaccine carriers is also covered. In light of the ongoing cases of severe and critical COVID-19, we also go over the recently developed prophylactics and treatments.
Keywords: COVID-19, alterations in strains, upcoming advancements, nanoparticles, nanotechnology, vaccinations.